2018
DOI: 10.1007/s12015-018-9803-3
|View full text |Cite
|
Sign up to set email alerts
|

Wharton’s Jelly Derived Mesenchymal Stem Cells: Comparing Human and Horse

Abstract: Wharton's jelly (WJ) is an important source of mesenchymal stem cells (MSCs) both in human and other animals. The aim of this study was to compare human and equine WJMSCs. Human and equine WJMSCs were isolated and cultured using the same protocols and culture media. Cells were characterized by analysing morphology, growth rate, migration and adhesion capability, immunophenotype, differentiation potential and ultrastructure. Results showed that human and equine WJMSCs have similar ultrastructural details connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In this respect, the proposed decellularized scaffolds evidenced a good growth and colonization by hUC-SCs. These cells are attractive for several tissue engineering applications, as they are derived from an ethically undisputed source and may be non-invasively harvested at low cost [36,37,38,39]. Our observation is in line with data of Xu et al [40], who showed a good proliferation for hUC-SCs cultured on medium-stiffness matrices.…”
Section: Discussionsupporting
confidence: 85%
“…In this respect, the proposed decellularized scaffolds evidenced a good growth and colonization by hUC-SCs. These cells are attractive for several tissue engineering applications, as they are derived from an ethically undisputed source and may be non-invasively harvested at low cost [36,37,38,39]. Our observation is in line with data of Xu et al [40], who showed a good proliferation for hUC-SCs cultured on medium-stiffness matrices.…”
Section: Discussionsupporting
confidence: 85%
“…TEM morphological analysis of MSCs showed ultrastructural details connected with the different origin of cells. A fibroblast shape morphology, dense nucleoli, a widespread Golgi apparatus and well developed RER are morphological features linked to the mesenchymal phenotype [41, 42]. Golgi complex and RER are strictly connected with a high protein synthesis and high metabolic rate [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…A fibroblast shape morphology, dense nucleoli, a widespread Golgi apparatus and well developed RER are morphological features linked to the mesenchymal phenotype [41, 42]. Golgi complex and RER are strictly connected with a high protein synthesis and high metabolic rate [41, 42]. The elevated secreting ability of these cells is further underlined either by the presence of several extracellular vesicles and exosomes, on cell surface, and multivesicular bodies, inside the cells, which are released in the extracellular microenvironment and act as paracrine factors [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult MSCs are localized in a special microenvironment, called the “niche”, that provides homeostasis, proliferative control, and the maintenance of cell number [11]. Since their first isolation from bone marrow [12,13], MSCs have been described in several other tissues, both from adult and fetal tissues, such as adipose tissue [14], dental pulp [15], periosteum [16,17], the umbilical cord [18,19], human synovial membrane (SmMSCs) [20], as well as in synovial fluid (synovial fluid mesenchymal stromal cells (SfMSCs)) [1].…”
Section: Introductionmentioning
confidence: 99%